Alexi Lalas, sensacion del futbol soccer = Alexi Lalas, soccer sensation - Kirkpatrick, Rob. (New York : Rosen Publishing Group's PowerKids Press & Buenas Letras, 2002)
Introduces the soccer star, Alexi Lalas.
Text in Spanish and English.
Includes bibliographical references and index.
Keywords: Lalas, Alexi; Soccer players -- Biography; Spanish language materials -- Bilingual